2006
DOI: 10.2174/157339906775473635
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenism, Insulin Resistance and Hyperinsulinemia as Cardiovascular Risk Factors in Diabetes Mellitus

Abstract: The polycystic ovary syndrome (PCOS) and hyperandrogenism are some of the most common endocrine disorders in women of fertile age. Insulin resistance is present in a significant proportion of hyperandrogenic patients, yet also, impaired beta-cell function, even in absence of clinically evident glucose intolerance, is a frequent finding, especially in patients with familial history of type 2 diabetes mellitus. Therefore, it is not surprising that hyperandrogenism, PCOS, and disorders of carbohydrate metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 121 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…In this review, all five studies reporting total daily insulin showed clinically significant reductions with a low-carbohydrate diet [ 8 , 10 , 22 , 24 , 26 ]. The excessive use of insulin that is often required to achieve glycaemic control in type 1 diabetes increases susceptibility to severe hypoglycaemia and may lead to some measure of hyperinsulinemia [ 29 ]. Hyperinsulinemia is associated with; excessive weight gain [ 30 ], development of the metabolic syndrome [ 31 ], inflammation and atherosclerosis [ 32 ], Alzheimer’s Disease [ 33 ] and cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, all five studies reporting total daily insulin showed clinically significant reductions with a low-carbohydrate diet [ 8 , 10 , 22 , 24 , 26 ]. The excessive use of insulin that is often required to achieve glycaemic control in type 1 diabetes increases susceptibility to severe hypoglycaemia and may lead to some measure of hyperinsulinemia [ 29 ]. Hyperinsulinemia is associated with; excessive weight gain [ 30 ], development of the metabolic syndrome [ 31 ], inflammation and atherosclerosis [ 32 ], Alzheimer’s Disease [ 33 ] and cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, women with PCOS have more severe IR than weight‐matched women without PCOS, suggesting that factors in addition to obesity may be involved in the development of IR (15). In addition to genetic factors, hyperandrogenemia (HA), which is observed in up to 74.2% of Chinese PCOS patients (16), may also be associated with the development of T2DM in PCOS patients (17). Glucose metabolic disorders, such as IR, have been found in PCOS patients with HA (18).…”
Section: Introductionmentioning
confidence: 99%
“…1 There are several shortcomings of the current treatment strategies for type 1 diabetes. These are the following: (1) only one of the underlying disease processes (insulin deficiency) is addressed, whereas other pathophysiologic contributors, such as excess glucagon, are not; (2) the most “rapid”-acting insulin currently available still peak in activity too late to perfectly match the postprandial glycemic peak, so every meal consumed leads to postprandial glucose spikes; (3) the doses of exogenous insulin needed to maintain metabolic control are supraphysiologic and lead to systemic hyperinsulinemia, which can contribute to low-grade inflammation (IL-6 and tumor necrosis factor α), obesity, vascular dysfunction, and possibly malignancy 24 ; and (4) obesity is an increasing problem in type 1 diabetes, which insulin only propagates. 5,6 Currently, the only noninsulin medication approved for use in type 1 diabetes is pramlintide, which delays gastric emptying and reduces postprandial glucagon secretion.…”
mentioning
confidence: 99%